INTERCOMPARISON OF PERFORMANCE OF RF COIL GEOMETRIES FOR HIGH FIELD MOUSE CARDIAC MRI - Constantinides, Christakis (2011)
Multi-turn spiral surface coils are constructed in flat and cylindrical arrangements and used for high field (7.1 T) mouse cardiac MRI. Their electrical and imaging performances, based on experimental measurements, simulations, and MRI experiments in free space, and under phantom, and animal loading conditions, are compared with a commercially available birdcage coil. Results show that the four-turn cylindrical spiral coil exhibits improved relative SNR (rSNR) performance to the flat coil counterpart, and compares fairly well with a commercially available birdcage coil. Phantom experiments indicate a 50% improvement in the SNR for penetration depths ≤ 6.1 mm from the coil surface compared to the birdcage coil, and an increased penetration depth at the half-maximum field response of 8 mm in the 4-spiral cylindrical coil case, in contrast to 2.9 mm in the flat 4-turn spiral case. Quantitative comparison of the performance of the two spiral coil geometries in anterior, lateral, inferior, and septal regions of the murine heart yield maximum mean percentage rSNR increases of the order of 27–167% in vivo post-mortem (cylindrical compared to flat coil). The commercially available birdcage outperforms the cylindrical spiral coil in rSNR by a factor of 3–5 times. The comprehensive approach and methodology adopted to accurately design, simulate, implement, and test radiofrequency coils of any geometry and type, under any loading conditions, can be generalized for any application of high field mouse cardiac MRI.